Representation of Nationalism Values in Information Texts of Indonesian Language Books For Grade III Elementary School - Kete, Sukadir; Karim; Dalman (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to examine the representation of nationalism values in informational texts of the Grade III Indonesian language textbook based on the Kurikulum Merdeka. Using a qualitative content analysis approach, the research focused on identifying key nationalism values such as patriotism, unity, appreciation of national symbols, and respect for cultural diversity. The primary data source was the textbook “Bahasa Indonesia: Kawan Seiring”, published by the Ministry of Education in 2022. The findings reveal that these values are presented both narratively and contextually, primarily through stories and descriptions of students’ everyday activities. Patriotism and cultural diversity appeared most frequently and were embedded in relatable and age-appropriate content. However, the textbook showed limited representation of national symbols and heroes, indicating a need for more balanced ideological content. Despite this gap, the study concludes that the textbook has the potential to support the internalization of civic and national values among elementary school students. By integrating character education into language learning, the book contributes not only to literacy development but also to shaping students’ national identity. These insights are expected to serve as valuable input for teachers, textbook writers, and policymakers in creating more value-oriented learning materials.